Comparative Research of Investment Value of Three Technology Companies - Zhu, Banghao (Transactions on Economics, Business and Management Research, 2024)
This article provides a detailed financial analysis of Intel, Northrop Grumman, and Qualcomm. The aim of this study is to gain insights into the effective investment strategies of these companies. The study included the analysis of the companies’ recent financial figures, such as exploring the meaning of various data, and exploring the asset selection challenges faced by four different investor types (including value, PEG, index, and momentum investors). By collecting, analyzing and comparing these data, this paper summarizes the trend of stock investment changes in the past and future. Leveraging established model, value investor tends to buy Intel, PEG investor will buy none of them, Index investor tend to buy Intel and Qualcomm, Momentum investor tends to buy NOC and Qualcomm. Furthermore, the insights gained from these analyses help develop tailored investment strategies, ultimately aiming to optimize financial gains in the technology sector and maximize returns on investment.